A review of Palaearctic Metachrostis Hübner, [1820] 1816 with description of three new species (Lepidoptera: Noctuidae, Eublemminae) - Kononenko, V. S.; Матоv, A. Yu. (Zootaxa, 2009)
Eleven of the thirteen Palaearctic species of the genus Metachrostis Hübner, [1820] 1816 are reviewed. Three new species, M. djakonovi sp. n., M. hoenei sp. n. and M. sinevi sp. n. are described from south east Kazakhstan and western Mongolia, south China, Sichuan Prov. and south of Russian Far East. Metachrostis miasma (Hampson, 1891), comb. n. and M. batanga (Draudt, 1950) comb. n. are transferred from the genus Eublemma to Metachrostis. The combination Eublemma melabela Hampson, 1910, comb. rev. for Metachrostis melabela is revalidated. Most treated species are redescribed and the adults and genitalia are illustrated. The genus Metachrostis is reported for the first time from Russia. A checklist of the genus Metachrostis is presented.